Accessibility Improvement Strategy to Support Tourism De-velopment of Lau Kawar Lake - Riyandi Hanafiah; Cut Nuraini; Abdi Sugiarto (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Lau Kawar Lake, a natural tourism area located on the slopes of Mount Sinabung in Karo Regency, North Sumatra, holds significant potential for the development of nature and culture-based tourism. However, the growth in tourist visits has not yet met expectations due to limited accessibility across various dimensions. This study aims to formulate strategies for improving physical, informational, and institutional accessibility in support of sustainable regional development.The research adopts a mixed methods approach, emphasizing primary data collection through field observations, interviews with key stakeholders and village officials, as well as surveys of 60 tourist respondents. Findings reveal that, overall, the three dimensions of accessibility are still rated as "fair," with average scores ranging from 3.28 to 3.36. The main barriers identified include inadequate road infra-structure within the area, lack of dedicated public transportation for tourists, limited official digital promotional content, and weak institutional coordination in area management. A synthesis of the quantitative and qualitative results indicates that the development of Lau Kawar Lake requires an integrative approach that combines spatial planning, community-based governance, and local policy interventions.Based on these findings, several strategic recommendations are proposed: (1) improvement of access roads and landslide-prone areas through Special Allocation Fund (DAK) for infrastructure; (2) provision of dedicated public transportation for tourists with fixed routes and schedules from the nearest city center; (3) installation of directional signs and visual information boards in aesthetically pleasing formats and bilingual language; (4) establishment of a Digital Promotion Team involving local actors and institutions; (5) capacity-building programs for the community in tourism services, home stay management, and culinary entrepreneurship; and (6) formation of a Cross-Sectoral Accessibility Coordination Forum for Lau Kawar Tourism as a medium-term planning and monitoring platform.This study contributes contextually to strengthening the accessibility dimension as a key prerequisite for advancing local tourism destinations towards sustainable, inclusive, and locally grounded development.